Pengaruh Realistic Mathematic Education (RME) Terhadap Kelancaran Prosedural Matematis Dan Motivasi Belajar Siswa - Anis Fitri Alimah; Dewi Azizah (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Mathematics is often considered a difficult and boring subject. However, with the right approach, mathematics can foster logical dan systematic thinking in problem-solving. This study aims to investigate: 1) the effect of RME approach on mathematical procedural fluency and student learning motivation, 2) the effect of RME approach on mathematical procedural fluency, 3) the effect of RME approach on student learning motivation. The method used was quasi-experiment with post-test only control group design. Research instruments included a written a test to measure procedural fluency, and a questionnaire to assess learning motivation. Data analysis techniques in this study used multivariate and univariate analysis with R software. The results showed that: 1) there is a significant difference simultaneously with Hotelling's T² test with p-value 0.02256 < 0.05, 2) there is a significant difference in procedural fluency with t-Independent test shows p-value 0.01019 < 0.05, 3) there is a significant difference in procedural fluency with Mann-Whitney test shows p-value 0.1249 > 0.05. These findings indicate that cognitive aspects and affective aspects have an attachment in achieving effective learning. Therefore, the RME approach can be considered an alternative learning strategy that teachers can use to develop residual mathematical abilities more optimally.